Classroom management strategies and motivation for teaching towards teaching effectiveness among physical education teachers in Southern Thailand - Tulyakul, Singha (2019)
Physical education in primary school is an essential course for developing the physical, emotional, spiritual and intellectual aspects of Thai students. However, through various reports, The Ministry of Education has found it to be ineffective. Further investigation it was found that many of the teachers were unable to manage classes efficiently, unmotivated to teach and unable to teach effectively. Therefore, research should be conducted to understand and manage those problems. The objectives of this study are to identify the level of classroom management strategies (CMS), the level of motivation for teaching (MT), and the teaching effectiveness (TE) among physical education teachers in Southern Thailand. Additionally, it also aims to examine the significant relationship between CMS, MT, and TE as well as to investigate whether MT plays the role of mediating effect on the relationship between CMS and TE among physical education teachers in Southern Thailand. Survey research design was conducted on 258 physical education primary school teachers in Southern Thailand. The instruments consisted of three questionnaires (classroom management strategies questionnaire, self-evaluation of teacher effectiveness questionnaire in physical education, and autonomous motivation for teaching questionnaire). The findings found that the level of CMS (M=4.06, S.D.=.37), MT (M=4.02, S.D.=.47), and TE (M=3.93, S.D.=.47) are high. Furthermore, this study found that there is a significant relationship between: CMS and MT (b=.44, p=<.05); CMS and TE (b=.44, p=<.05); MT and TE (b=.36, p=<.05). This study also found that MT plays an important role as the mediating effect between CMS and TE among physical education teachers in Southern Thailand. (b=.16, p=<.05). From these findings, it is recommended that to improve physical education’s teaching effectiveness, physical education teachers should enhance their ability in classroom management strategies and develop their intrinsic motivation in teaching.